How does green finance influence industrial green total factor productivity? Empirical research from China - Hu Yue; Zizhuo Zhou; Hanwen Liu (Energy Reports, 2024)
Industry is the pillar of the real economy, and its green development contributes to achieving the green and low-carbon development goals proposed by the United Nations. This paper constructs an analytical framework of ''green finance-green technological innovation-industrial green total factor productivity'' to study how green finance (GF) influences industrial green total factor productivity (IGTFP). Based on the panel data from 30 provinces and 281 cities in China between 2011–2019，this study measures the GF levels and the IGTFP index by using the entropy method and super-efficiency slacks-based model with Malmquist-Luenberger index method, to conduct a series of empirical tests. Also, we focus on the mechanism effect of green technology innovation (GTI) in the process of GF affecting IGTFP. Additionally, we have discussed the supporting role of digital financial inclusion (DFI) in green finance development at the micro level. The main findings include: (1) The development of green finance (GF) can significantly improve IGTFP, and it’s still credible after a series of robustness tests. (2) The heterogeneity analysis indicates that the influence of GF on the IGTFP varies from different cities, and this positive effect tends to increase with the expansion of city size. (3) Mechanism tests show that green technological innovation (GTI) has a positive mechanism effect in the process of GF influencing IGTFP. (4) The discussion indicates that digital financial inclusion can support green finance development, so as to promote industrial green development in China. This study has momentous theoretical value and policy implications for China and other developing countries in exploring green finance and industrial green development.